Chemoresistance is associated with Beclin-1 and PTEN expression in epithelial ovarian cancers - YING, HUANCHUN (Oncol Lett, 2015)
The aim of the present study was to investigate the protein expression of the autophagy-related genes, BECN1 and PTEN, and the association with drug resistance in epithelial ovarian cancers. In total, 40 patients with pathologically diagnosed epithelial ovarian cancer were divided into a chemotherapy-sensitive group (n=20) and a chemotherapy-resistant group (n=20), according to the results of the pre- or post-operative normative chemotherapy and the post-operative follow-up. The protein expression of the phosphatase and tensin homolog (PTEN) and the BECN1 gene product, Beclin-1, was analyzed using immunohistochemistry in the 40 patients with ovarian carcinoma. The positive rate of Beclin-1 expression was significantly lower in the resistant group (35.0%) compared with the sensitive group (50.0%). The positive rate of PTEN expression was also significantly lower in the resistant group (30.0%) compared with the sensitive group (65.0%). Furthermore, the differences in the expression rates were revealed to be significant (P<0.05). The expression of Beclin-1 was identified to be positively correlated with the expression of PTEN (rs=0.816; P<0.0001). The low expression of the Beclin-1 and PTEN proteins in the ovarian cancer tissues was revealed to be closely associated with drug resistance. Therefore, Beclin-1 may interact with PTEN to participate in the mechanism of drug resistance and the changes in macrophage activity observed in cases of drug-resistant ovarian cancer.